DESIGN OF STATE CONTROL REGULATIONS IN MINERAL MINING VALUE ADDED ACTIVITIES - Akmaluddin Rachim (NOMOI Law Review, 2020)
The Constitutional Court has given the Constitutional Court the interpretation of state control or the right to control as a guide in mineral mining governance activities.The problem arises when thisestimate has not been able to be properly implemented in mineral mining governance arrangements.The presence of Law no.3 of 2020which isexpected to have implications for the greatest possible prosperity of the people with the presence of a form of full state controlin activities to increase added value has not been able to answer this problem.This study aims: (1) to determine whether theregulation of the concept of state control has been accommodated in value added activities as regulated in Law no.3 of 2020, (2) to determinethe appropriatedesign fortheconcept of state control to achieve the goal of state control.This research is a normative legal research.The research was conducted by means of a literature study that examinesprimary and secondary legal materialsand uses aconceptual approach.The data that has been collected were analyzed using descriptive qualitative methods.The results of this study concluded that: (1)Regulation of the concept of state control has not been accommodated in value added activities as regulated in Law no.3 of 2020. Even the right to control the state as interpreted by the Constitutional Court tends to be ignored.(2)The regulatory design for the concept of state control that is appropriate for achieving the goal of state control is that it must have a strong legal and institutional substance and have a vision for Indonesia's industrialization in the future.The substance of the law must refer to the mandate of Article 33 paragraph 3 of the 1945 Constitution and the sustainable institutional management model.